COMENTARIOS SOBRE LA INVESTIGACIÓN CIENTÍFICA - Hurtado Dianderas Smith, Eulogio (2006)
In the current article we wrote some reflections on scientific research, like thematic, emphasizing his conceptualization and relatioship to creativity and innovation, with the purpose of motivating the readers into the studying of scientific research. The current text looks for to define the complex network of scientific research concatening knowledge, creativity an academic world; in scientific development, in technology and as a discipline. Which is why we took some reflections from the great minds in this area, arriving to the conclusion that the scientific research is a process that does not follow a way traced up before in all its details, or a unique path that must be crossed on blind or mechanically, and whose purpose is to obtain the truth at the end of the path. The method is a wire that guides the scientific work; that is why it is affirmed that research is a process that is constructed as we go through, where there are sufficient paths left by other scientists for not to lose oneself an that are in danger to be covered by the weeds of social life complexity. Finally, I want to express that scientific method is neither the more nor the less than the way to make good science, natural or social, pure or applied, formal or factic and that can be adapted to fields that before were not scientific because they are characterized, like science, for the search of general guidelines.